2018
DOI: 10.1155/2018/8393194
|View full text |Cite
|
Sign up to set email alerts
|

Basic Fibroblast Growth Factor Fused with Tandem Collagen-Binding Domains from Clostridium histolyticum Collagenase ColG Increases Bone Formation

Abstract: Basic fibroblast growth factor 2 (bFGF) accelerates bone formation during fracture healing. Because the efficacy of bFGF decreases rapidly following its diffusion from fracture sites, however, repeated dosing is required to ensure a sustained therapeutic effect. We previously developed a fusion protein comprising bFGF, a polycystic kidney disease domain (PKD; s2b), and collagen-binding domain (CBD; s3) sourced from the Clostridium histolyticum class II collagenase, ColH, and reported that the combination of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Collagen materials have been used for the sustained release of rhBMP-2 in clinical settings [9][10][11]. We previously reported that collagen-like polypeptide poly(POG)n is superior to animalderived collagen with regard to thermal stability and lack of pathogenicity and is a useful carrier which retains bFGF well [17,18]. Our preliminary study showed that 2.0 μg of rhBMP-2 without poly(POG)n failed to promote bone formation in a mice bone defect model.…”
Section: Implants Segmental Mousedismentioning
confidence: 90%
See 1 more Smart Citation
“…Collagen materials have been used for the sustained release of rhBMP-2 in clinical settings [9][10][11]. We previously reported that collagen-like polypeptide poly(POG)n is superior to animalderived collagen with regard to thermal stability and lack of pathogenicity and is a useful carrier which retains bFGF well [17,18]. Our preliminary study showed that 2.0 μg of rhBMP-2 without poly(POG)n failed to promote bone formation in a mice bone defect model.…”
Section: Implants Segmental Mousedismentioning
confidence: 90%
“…We previously reported that the artificial collagen-like peptide poly(POG)n was a useful carrier for growth factors. Injection of bFGF-loaded poly(POG)n into fracture sites stimulated periosteal bone formation in mouse fracture models [17,18]. In the present study, we investigated whether a single injection of rhBMP-2-loaded artificial collagen-like peptide gel (rhBMP-2/ACG) accelerates consolidation at the bone defect site and bone union at the docking site in a mouse SBT model.…”
Section: Introductionmentioning
confidence: 98%
“…The femur fracture model was generated using 9-week-old C57BL/6 J mice [ 19 ]. The mice were maintained at Nippon Charles River Laboratories (Kanagawa, Japan) in a semi-barrier system under controlled temperature (23 ± 28 °C), humidity (55 ± 10%), and lighting (12-h light/dark cycle), and received standard rodent chow (CRF-1; Oriental Yeast, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…For example, a bacterial collagen-binding domain (CBD), was fused to fibroblast growth factor-2 (FGF-2), allowing improved bone formation in a spinal fusion model (Inoue et al, 2017). In another study, CBD-fused FGF-2 showed the ability to induce significantly higher mesenchymal cell proliferation and callus formation in a mice fracture model compared to wild-type FGF-2 (Sekiguchi et al, 2018). Similarly, a CBD-fused hepatocyte growth factor (HGF) delivered via hydrogel improved recovery after spinal cord injury in mice compared to wild-type HGF (Yamane et al, 2018).…”
Section: Engineering Gfs For Non-covalent Interaction To Biomaterialsmentioning
confidence: 99%